Evaluasi Kesesuaian Lahan Untuk Tanaman Ubi Kayu (Manihot esculenta) di DAS Gufasa - Risdyanti Edy; Asrul Ali Hasan; Adnan Sofyan (Universitas Khairun, 2022)
Land evaluation is the process of assessing the appearance of land for a specific purpose, including conducting and interpreting surveys and studies of land forms, soils, vegetation, climate, and other land aspects in order to identify and make comparisons of various land uses that might be developed. The aims of this study were: to determine land suitability classes and their management for cassava in the Gufasa watershed of Dodinga Village, South Jailolo District, West Halmahera Regency. This research took place from October to November 2021. Evaluation of land suitability refers to the FAO land suitability classification system (1976) to the category of land suitability units. There are two land suitability conditions presented, namely actual land suitability (A) and potential suitability (P). The actual land suitability for cassava plants in the Gufasa Watershed of Dodinga Village is suitable (S) with an area of 496.6 Ha (35.21%) and not suitable (N) with an area of 913.6 Ha (64.78%) with limiting factors, namely very obstructed drainage, flooding heavy (flood hazard), rough texture, heavy erosion and slopes 15%. Suitable land (S) is divided into two classes, namely quite suitable (S2) with an area of 108.0 Ha (7.6%) with a limiting factor of rainfall, rather fine texture, low total N, and mild erosion and marginally suitable (S3) with an area 388.6 Ha (27.55%) with a very low limiting factor of N-total and slope. Potential land suitability for cassava plants if efforts to improve the land limiting factors are obtained that are suitable (S) of 360.8 Ha (28.31%) and unsuitable (N) of 913.6 Ha (7.15%).Keywords: Land suitability, land characteristics, soil quality, limiting factors